Evaluation of The Use of De-Oiled Sunflower Meal Protein Powder in Mini Frankfurter-Type Chicken Sausage - Ermiş, Ertan; Ermiş, Ertan (İlknur BAĞDATLI, 2024)
This research aimed to evaluate the effect of the protein powder (SPP) obtained from de-oiled sunflower meal, a by-product of sunflower oil extraction, on the physicochemical, textural, and sensory properties of mini frankfurter-type chicken sausage. The extracted proteins from the sunflower meal were added to the sausage formulation at 1% concentration, and the SPP-added sausage sample was compared with the control sample. The incorporation of SPP increased hardness, chewiness, and cohesiveness properties compared to the control sausages and slightly improved sensory attributes. The results suggest that SPP may serve as a promising ingredient to improve the quality parameters of emulsified meat products.
Keywords: Protein powder; Sunflower meal; by-product valorisation; Chicken sausage